Surgical Service Nosocomial Infections at a Veterans Administration Medical Center - Hinahon, Jaime (1988)
Nosocomial surgical infections at a Veterans Administration medical center were monitored from February 1986 to June 1987 (17 months). Three hundred twenty-four patients had 508 nosocomial infections, including 66 patients in whom cultures were not performed. The remaining 258 patients had 584 microorganisms, including gram-negative bacilli (56.8 percent), gram-positive cocci (33.6 percent), and yeasts (8.4 percent). The most common isolates were Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, group D enterococci, and Staphylococcus epidermidis. Antimicrobial susceptibilities were similar for nosocomial and all hospital isolates combined 84.5 percent of the time; all hospital isolates combined were more resistant in 5.5 percent and nosocomial isolates in 10.0 percent. The infection rate for surgical wounds was only 2.5 percent. When all nosocomial infection sites were compared, however, the rate for lower respiratory tract and some other infections appeared high and disproportionate. The significance of this finding is questionable because of a lack of comparable published reports from other Veterans Administration medical centers. The importance of patient population at risk of obtaining some nosocomial infections (especially lower respiratory) may be greater in adult men than in other patient populations.